Cultures in conflict : a documentary history of the Mormon War in Illinois - Hallwas, John E.; Launius, Roger D. (Utah State University Press, 1995)
Cultures in Conflict offers students of history an invaluable source of documents regarding the history of the Mormon presence in Illinois. Few local histories are so academically sound.-Illinois TimesHallwas and Launius have compiled and written the most balanced and thorough account yet of the events and circumstances that led to the forced Mormon exodus from Nauvoo following the mini civil war that erupted in Illinois during the 1849s.